2019
DOI: 10.1111/cid.12833
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the clinical outcomes of peri‐implant tissues in patients treated for peri‐implant mucositis and followed up for 54 months

Abstract: Background Peri‐implant mucositis is very common and, when left untreated, can progress to the more serious condition of peri‐implantitis. Therefore, early diagnosis, adequate treatment and, in particular, adherence to a peri‐implant supportive therapy are extremely important for the management of peri‐implant mucositis. Purpose Characterize the clinical conditions of peri‐implant tissues in patients diagnosed with peri‐implant mucositis after undergoing peri‐implant supportive therapy for 54 months. Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Perussolo et al were considered, respectively, at moderate and high risk of bias, 21,30 respectively. Finally, half of the prospective cohort studies demonstrated low risk of bias, 4,29 while two studies 25,28 demonstrated high risk of bias.…”
Section: Quality Of the Evidence And Risk Of Bias Assessmentmentioning
confidence: 95%
See 4 more Smart Citations
“…Perussolo et al were considered, respectively, at moderate and high risk of bias, 21,30 respectively. Finally, half of the prospective cohort studies demonstrated low risk of bias, 4,29 while two studies 25,28 demonstrated high risk of bias.…”
Section: Quality Of the Evidence And Risk Of Bias Assessmentmentioning
confidence: 95%
“…Five of the studies were prospective cohort studies, 4,21,25,28,29 three were non-RCTs, 26,27,30 and one was an RCT. 20 Seven studies were carried out solely in academic settings, 20,21,[26][27][28][29][30] while the remaining two were conducted in both academic and private practice settings. 4,25 All but one of the studies 4 were single-centered clinical trials.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations